Gamma-glutamyl-leucine levels are causally associated with elevated cardio-metabolic risks - Wu, Qiong; Li, Jiankang; Zhu, Jinghan; Sun, Xiaohui; He, Di; Li, Jun; Cheng, Zongxue; Zhang, Xuhui; Xu, Yuying; Chen, Qing; Zhu, Yimin; Lai, Maode (Frontiers in Nutrition, 2022)
Objective: Gamma-glutamyl dipeptides are bioactive peptides involved in inflammation, oxidative stress and glucose regulation. Gamma-glutamyl-leucine (Gamma-Glu-Leu) has been extensively reported to be associated with the risk of cardio-metabolic diseases, such as obesity, metabolic syndrome, and type 2 diabetes. However, the causality remains to be uncovered. The study aimed to explore the causal-effect relationships between Gamma-Glu-Leu and metabolic risk. Methods: In this study, 1289 subjects were included from a cross-sectional survey on MetS in eastern China. Serum Gamma-Glu-Leu levels were measured by untargeted metabolomics. Using linear regressions, a two-stage genome-wide association study (GWAS) for Gamma-Glu-Leu was conducted to seek its instrumental SNPs. One-sample Mendelian Randomization (MR) analyses were performed to evaluate the causality between Gamma-Glu-Leu and the metabolic risk. Results: Four SNPs are associated with serum Gamma-Glu-Leu levels, including rs12476238, rs56146133, rs2479714 and rs12229654. Out of them, rs12476238 exhibits the strongest association (Beta=-0.38, S.E. =0.07 in discovery stage, Beta=-0.29, S.E. =0.14 in validation stage, combined P-value =1.04×10-8). Each of the four SNPs has a nominal association with at least one metabolic risk factor. Both rs12229654 and rs56146133 are associated with body mass index, waist circumference (WC), the ratio of WC to hip circumference, blood pressure and triglyceride (5×10-50.05). Conclusion: Four SNPs (rs12476238, rs56146133, rs2479714 and rs12229654) may regulate the levels of serum Gamma-Glu-Leu. Higher Gamma-Glu-Leu levels are causally linked to cardio-metabolic risks. Future prospective studies on Gamma-Glu-Leu are required to explain its role in metabolic disorders.